From Hospital to Home: PT Griyakami's Marketing Strategy to Reach Home Care Customers - Neng Ima Rahmayanti; Eko Wulandari; Nur Hayati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The homecare industry is experiencing rapid growth; however, there remains a gap in the literature concerning the application of multidimensional marketing strategies, particularly among private providers such as PT Griyakami. Most previous studies have focused on hospital-based service promotion, overlooking the tailored approaches required in homecare settings. This study aims to fill that gap by identifying and analyzing the most effective marketing strategies in the homecare industry, especially for customer acquisition and retention in digital contexts. Using a Systematic Literature Review (SLR) of 30 indexed articles (2016–2024) from Google Scholar and analyzed through VOSviewer, this study reveals thematic trends in homecare marketing strategies. The findings indicate that digital-based strategies—such as social media campaigns, telemedicine integration, and online service personalization—are significantly correlated with increased brand awareness and customer conversion. Strategic collaborations with healthcare institutions and educational approaches are also shown to enhance customer trust and loyalty. Post-2020 research trends reveal a shift toward digital health innovation, highlighting the importance of adaptive, technology-driven marketing strategies. Based on these findings, this study recommends that PT Griyakami implement a data-driven, multichannel marketing strategy, including: (1) development of a digital platform integrated with HMIS and registration features; (2) partnerships with midwives and BPJS to expand outreach; (3) flexible pricing models based on patient segmentation; and (4) structured performance monitoring using KPIs and customer satisfaction surveys. These strategic recommendations provide a practical roadmap for PT Griyakami to enhance competitiveness, improve service personalization, and achieve sustainable growth in the homecare sector.